ANALISIS DEFLEKSI LATERAL DAN PENURUNAN PONDASI TIANG PANCANG BAJA PADA ABUTMENT JEMBATAN : STUDI KASUS JEMBATAN SEI ELLA 1 - Kohar Yudoprasetyo; Moh. Fadhlan Rosyidi; Ifarrel Rachmanda Hariyanto; Naura Firdausi; Moh. Safi’i Mansur; Khansa Fadilah Ashara; Yosi Noviari Wibowo; Mohammad Akbar Alrasyidi (CV SWA Anugerah, 2025)
This study aims to evaluate the performance of steel pile foundations for the abutment of the Sei Ella 1 Bridge, located at the Ela River, West Kalimantan, with soil conditions consisting of sedimentary layers. The analysis was conducted based on actual piling conditions, where pile depths vary between 4.015 meters and 5.823 meters. The evaluation includes calculating the single pile bearing capacity using the Decourt method, analyzing group pile capacity with the efficiency group approach, and assessing lateral deformation and settlement using the Finite Element Method (FEM). The results show that the single pile and group pile capacities are sufficient to withstand the loads from the superstructure, abutment self-weight, and lateral soil pressure. The lateral deformation analysis yielded a deflection value of 2.83 mm, while the settlement was recorded at 0.1152 mm. Both values are well below the maximum limit set by SNI 8460:2017, which is 12.5 mm, indicating that the foundation is in a safe and stable condition. This study provides a deeper understanding of the performance of steel pile foundations for the abutment of the Sei Ella 1 Bridge. As an additional verification step, it is recommended to conduct Static Loading Tests (compressive, tensile, and lateral) to validate the analysis results. This approach offers a robust foundation for ensuring the safety, stability, and feasibility of the design under actual conditions..